Interactions with the integrative memory model. (3rd January 2020) - Bastin, Christine; Besson, Gabriel; Delhaye, Emma; Folville, Adrien; Geurten, Marie; Simon, Jessica; Willems, Sylvie; Salmon, Eric
Abstract: The integrative memory model formalizes a new conceptualization of memory in which interactions between representations and cognitive operations within large-scale cerebral networks generate subjective memory feelings. Such interactions allow to explain the complexity of memory expressions, such as the existence of multiples sources for familiarity and recollection feelings and the fact that expectations determine how one recognizes previously encountered information.